Virtual Interviews Are Not Adequate Replacements for In-Person Interviews for Orthopaedic Sports Medicine Fellowship Program Directors and Applicants - Grace Tanguilig, B.S; Matthew J. Kraeutler, M.D; Mary K. Mulcahey, M.D (Elsevier, 2024)
Purpose: To understand the opinions of both orthopaedic sports medicine fellowship program directors (PDs) and applicants regarding the utility of virtual interviews in comparison to in-person interviews following the 2022-2023 application cycle. Methods: An anonymous online survey was distributed through the American Orthopaedic Society for Sports Medicine to applicants and PDs of orthopaedic sports medicine fellowship programs. Questions in the survey included how the virtual format affected the applicants' personal connection to the program, the interview day structure, and costs associated with the interview process. Results: Responses were received from 69 of 93 PDs (74%) and 97 of 266 applicants (36%). Ninety-five percent of PDs (59 of 62) preferred in-person interviews, compared to 79% of applicants (70 of 89). Ninety-eight percent of PDs (60 of 61) and 82% of applicants (72 of 88) thought it was important/very important to interview in-person. Sixty-one percent of PDs (35 of 57) and 49% of applicants agreed/strongly agreed that conducting virtual interviews negatively affected their personal connection with the fellowship interviewee/program. The presence of virtual interviews allowed 50% (43 of 86) of applicants to go on more interviews. Thirty-two percent (18 of 57) of fellowship programs saved up to $5,000 conducting virtual interviews, and 85% (69 of 81) of applicants saved up to $5,000 on travel expenses by attending virtual interviews. Conclusions: Virtual interviews allow fellowship applicants to complete more interviews and presented financial savings for both programs and applicants. However, both PDs and applicants stated that interviewing in-person is essential for applicants to meet faculty and tour the facilities. Clinical Relevance: This study may be valuable to fellowship programs considering continued use of virtual interviews.